PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN MATEMATIKA (Jurnal Penelitian, 2013)
This study aimed to determine: (1) how was the design of character building by learning mathematics, and (2) whether the character building by learning mathematics could produce better learning outcome of mathematics than conventional mathematics learning. To answer these two questions, I used Research and Development (R & D) which consists of a preliminary study to obtain preliminary data on student learning outcomes before being given treatments of character building by learning mathematics. The next phase is the design of the character building by learning mathematics. Further testing and revision in class and repeated until it found the best learning model. From the first problem formulation, qualitative data analysis, such as the design of character building in learning mathematics was produced. The results of the qualitative analysis shows, character building by learning mathematics was quite effectively applied to implant positive character in students. To answer the second question, statistical analysis was used. The population in this study was all students of class VII of MTsN in Buaran of Pekalongan which totaled 220. By random cluster sampling technique two classes (a class VII A and VII B) was chosen. Class VII A was as an experiment class, and class VII B was as a control class. Data were taken by the test method, experimental classroom observation, and documentation. The data was then processed with an average difference test. Results of statistical analysis obtained t = 3.33 > t table = 1.67. This meant that learning achievement of the students in the experimental class, which was implemented character education in mathematics was better than the students who were taught by conventional methods. Based on these results, it could be conclude that the character building in mathematics was better than the conventional method of learning mathematics.
Keywords: pendidikan karakter, pembelajaran matematika, prestasi belajar